Perkembangan Tingkat Pengembalian Investasi Pendidikan Menengah di Sumatera Barat - Stevannie Dwi Cahya; Hasdi Aimon (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This study aims to determine the rate of return on investment in secondary education in West Sumatra and analyze the effect of education, experience, gender, residence, marital status and children on the rate of return on investment in education in West Sumatra. This study uses secondary data sourced from the 2018 and 2020 National Labor Force Survey (SAKERNAS) by the Central Statistics Agency (BPS). With the dependent variable in this study using the rate of return on education investment. The independent variables consist of education, experience, gender, residence, marital status, and children. This study uses multiple linear regression methods with cross section data in West Sumatra in 2018 and 2020. The results showed that the rate of return on education investment in West Sumatra in 2018 and 2020 both showed an increase with increasing levels of education. In 2018 and 2020, the variables of education, experience, gender, residence, and marital status all have a positive and significant influence on the rate of return on education investment in West Sumatra. While the child variable has a negative and significant influence on the rate of return on education investment in West Sumatra.